34.3k views
4 votes
Please help!!

2. Solve x^2 - 6x = -5 by completing the square.

Show all work for the steps below.

(a) For x^2 - 6x + c = -5 + c, what value of c is used to complete the square?

(b) Substitute the value for c in Part 2(a). Then complete the square to rewrite the equation as the square of a binomial.

(c) Solve for x.

User Carlos N
by
5.9k points

1 Answer

2 votes

Answer:

c=9

(x-3)^2 = 4

x= 1,5

Explanation:

x^2 - 6x = -5

Take the coefficient of x

-6

Divide by 2

-6/2 = -3

Square it

(-3)^2 = 9

Add this to each side

x^2 - 6x + 9 = -5 + 9

x^2 -6x+9 = 4

(x-3)^2 = 4

Take the square root of each side

sqrt((x-3)^2) = ±sqrt(4)

x-3 = ±2

Add 3 to each side

x-3+3 = 3±2

x = 3+2 x = 3-2

x =5 x=1

User Gamer
by
5.0k points